EXPERIMENTAL AND THEORETICAL STUDIES OF THE OPERATION OF THE BUSHES OF DRILLED MICROPILES UNDER THE ACTION OF HORIZONTAL LOADS - Hnatiuk, О.; Lapchuk, М. (Bulletin of Lviv National Environmental University. Series «Architecture and Construction», 2024)
The use of pile foundations during reconstruction and in densely built-up areas is complicated by the fact that there is no possibility of using large-sized machines and mechanisms. Therefore, especially in cases of complex engineering and geological conditions, the use of micropiles, which are made with the help of small-sized equipment, can be quite effective, in particular, for the foundations that perceive horizontal loads (retaining walls, sheet pile rows, etc.). At the Department of Building Structures of LNUP, a new effective design of drilled reinforced concrete micropiles with a spread heel was developed and implemented in real construction, and a methodology for researching their operation under the action of horizontal shear loads with crushed stone was developed. Experimental studies have been conducted and the results of experimental full-scale tests of micropile bushes with different types of artificial backfill of different heights on the action of horizontal loads have been shown, and the dependence of their movements on the action of shear forces has been shown. Theoretical calculations of the stresses and deformations of micropiles in real soil conditions were carried out and their comparison with experimentally obtained data was carried out. The proposed design of micropile bushes is effective when using it as a retaining wall. The results of experimental studies indicate that when installing retaining walls, it is recommended to arrange an artificial pillow of coarse-grained materials, and it is recommended to take the minimum thickness of the backfill layer in accordance with the structural requirements and the actual engineering and geological situation of the construction site. The construction of the retaining wall using reinforced concrete micropiles with a spread heel is implemented in the PP BKF «Osnova» at construction and reconstruction sites in the city of Lviv and Lviv region.